Comparative Study of Synthetic Insecticides with Biopesticides against Spotted Stem Borer, Chilo partellus (Swinhoe) on Maize (Zea mays L.) - Abhishek Garhwal; Usha Yadav (Archives of Current Research International, 2024)
Spotted stem borer, Chilo partellus (Lepidoptera: Pyralidae) regarded as one of the most significant and prevalent insect pests of maize and its mystic aspect of feeding makes it challenging to control. Hence current study aims to evaluate comparative study of synthetic insecticides with biopesticides against Chilo partellus. Eight treatments viz., azadirachtin 10,000ppm, neem oil 3%, karanj oil 3%, neem oil 3% + imidacloprid 17.5%SL, karanj oil 3% + imidacloprid 17.5%SL, imidacloprid 17.5%SL, spinosad 45%SC and untreated control were tested under field condition in randomized block design with three replications. Among the treatments, lowest larval population of Chilo partellus per plant were recorded in karanj oil 3% + imidacloprid 17.5%SL (1.99) followed by neem oil 3% + imidacloprid 17.5%SL (2.42), imidacloprid 17.5%SL (2.71), spinosad 45%SC (3.17), neem oil 3% (3.73), karanj oil 3% (3.95) and azadirachtin 10,000ppm (4.44) were found superior over the untreated control (7.24). The highest yield was recorded in karanj oil 3% + imidacloprid 17.5%SL with 39.20 q/hectare and most economic treatment was imidacloprid 17.5%SL with highest cost benefit ratio (1:2.2). The lowest cost benefit ratio was recorded in untreated control (1:1.4).